Collaborative Problem Based Learning to Improve Metacognitive of Chemistry Students: Systematic Literature Review - Rusly Hidayah; Fauziatul Fajaroh; Parlan Parlan; I Wayan Dasna (STAI Hubbulwathan Duri, 2022)
While collaborative problem-based learning (PBL), particularly in Western nations, has been researched and shown to be beneficial in enhancing students' metacognitive skills, it is still sparingly used in Asian nations like Indonesia. This study's goal was to learn more about the potential benefits of cooperative PBL on students' metacognitive skills. The systematic literature review (SLR) research design was used for this study, and the requirements were full text, journal articles, open access, accredited national and international publications between 2010 and 2020, and articles on the role of collaborative PBL in chemistry students' metacognitive development. The findings of the SLR used in this study show that PBL enhances students' metacognitive skills, particularly in chemistry students. The majority of research, however, continues to employ unreliable, nonstandard methods. Therefore, it is believed that this research may be used as supplemental data to acquire in-depth PBL findings.